Allergic rhinitis and dental-supporting tissue diseases in children. Issue 7 (19th February 2021) - Lai, Wan-Yu; Wei, Chang-Ching; Wan, Lei; Mai, Chen-Hao; Lin, Cheng-Li; Tsai, Jeng-Dau
Abstract : Abstract: The etiology of dental-supporting tissue diseases in children is multi factorial and not merely related to oral hygiene. Therefore, in the present study, we investigated the relationship between children <18 years old with allergic rhinitis (AR) and the risk of dental-supporting tissue diseases. Data from the National Health Insurance Research Database (NHIRD) of Taiwan were used to conduct a retrospective longitudinal cohort study. The study cohort comprised 378, 160 patients with AR (AR group) and 378, 160 patients without AR (non-AR group), who were selected through frequency matching based on age, sex, and the index year. The study patients were followed until dental-supporting tissue diseases occurrence, withdrawal from the National Health Insurance program, or December 31, 2013. Cox proportional hazards regression analysis was conducted to calculate the risk of dental-supporting tissue diseases in the AR group after adjustment for age, sex, and relative comorbidities. The adjusted HRs of periodontal, pulp, and periapical diseases in AR children were higher than those in the non-AR controls (1.51, 95% CI: 1.50 to 1.53; 1.06, 95% CI: 1.05 to 1.07, respectively). The AR to non-AR HRs of these inflammatory dental diseases were particularly higher in children <6 years old and in boys. The HRs of periodontal, pulp, and periapical diseases were greatest in those with >5 AR-related medical visits/year (5.57, 95% CI: 5.50 to 5.56; 4.06, 95% CI: 4.00 to 4.12, respectively). Children with AR had a greater risk of inflammatory dental-supporting tissue diseases, particularly those <6 years old with primary teeth, boys, and those with severe persistent AR.